2008
DOI: 10.1074/jbc.m806897200
|View full text |Cite
|
Sign up to set email alerts
|

The Cotranslational Maturation Program for the Type II Membrane Glycoprotein Influenza Neuraminidase

Abstract: The earliest steps in nascent protein maturation greatly affect its overall efficiency. Constraints placed on maturing proteins at these early stages limit available conformations and help to direct the native maturation process. For type II membrane proteins, these cotranslational constraints include N-and C-terminal membrane tethering, chaperone binding, and disulfide bond formation. The cotranslational maturation process for the type II membrane glycoprotein influenza neuraminidase (NA) was investigated to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 55 publications
1
44
0
Order By: Relevance
“…Previous work demonstrated that NA rapidly dimerizes within ϳ2.5 min and this can occur co-translationally (25,27). Additionally, conformation specific antibodies revealed a unique time lag of ϳ5 min between NA oligomerization and when NA reached its native tetrameric conformation (25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work demonstrated that NA rapidly dimerizes within ϳ2.5 min and this can occur co-translationally (25,27). Additionally, conformation specific antibodies revealed a unique time lag of ϳ5 min between NA oligomerization and when NA reached its native tetrameric conformation (25).…”
Section: Discussionmentioning
confidence: 99%
“…NA oligomerization occurs rapidly and efficiently within the endoplasmic reticulum, possibly through an N-terminal directed process (25)(26)(27). However, the direct role of the TMD in NA assembly has received little attention.…”
mentioning
confidence: 99%
“…As small proteins may be able to fold without the assistance of chaperones, it would be of interest to determine if glucosidase II trimming can be controlled to by-pass lectin chaperone binding so that these chaperones can focus their attention on more complex proteins that require their assistance for proper maturation. The number and location of glycans appears to dictate to some extent the molecular choreography or the chaperone binding profile for the individual chaperones (Hebert et al, 1997, Molinari and Helenius, 2000, Wang et al, 2005, Wang et al, 2008). While non-glycosylated proteins or regions may be aided by the Hsp70 chaperone BiP and protein disulfide isomerase family members such as PDI, glycans provide the dominant chaperone signal.…”
Section: Getting Started: Translocation and Early Maturation Eventsmentioning
confidence: 99%
“…The necessity of a modification at a specific site is highly protein and site dependent. Whereas some sites of modification are absolutely required for efficient maturation, others are completely dispensable (Hebert et al 1997;Wang et al 2008). Sometimes the location is not critical but the total number of glycans is.…”
Section: N-linked Glycosylationmentioning
confidence: 99%